Factors of the collapse of civilizations as portrayed by Quranic stories in Surat Al- Hijr and the world's neglect of them - Al Ameri, Khalifa bin Saif bin Humaid (Journal of Humanities & Social Sciences, 2018)
Surah in the Holly Koran called Surah Al Hajr ,is No.15 of the Koran Surah's, This Surah came to guide people to the right or to know God AlmightyThis Surah was revealed in Mecca before the migration of the Prophet Mohammed from Mecca to Medina, where it came during a critical and harsh period at the life of the Prophet Muhammad (Peace Be Upon Him) , that year his uncle Abu Talib died-  and his wife Khadija Bint Khuwaylid (May Allah pleas her) also died The story of Adam creation (Peace Be Upon Him) came in (Al Hajr) Surah events, as also four other stories about previous nations and civilizationsThrough these stories of Al Hajr- Sura referred to both the material construction and the civilization building in these four civilizations, as well as the progress, prosperity and prosperity of these nations and people, showed the civilizations of such extravagance, generosity and luxury which ultimately led to committing sins, corruption and injustice. Deserved the torment of God and after the torment these civilizations become nonexistentThe Holy Quran guides every country or nation confused to signs of good and reconciliation for all human beings, because the main goal of the Holy Quran came to achieve this honorable and noble goals.There are a lot of people waiting for who ignites his torch of light until his life shines and lights his way up to the right path of security, comfort and reassurance. Because man is the first intended and the basic goal of the Koran descent.The effects of storytelling has a profound impact on those who hear these stories, and used the Koran storytelling to make for them a method of education and advocacy to God (Glory be to Him) In this way, through storytelling, the effects of these stories have great effect and benefits.But now most of the worlds nations today achieved the factors civilizations collapse and inattention (such as the civilizations stories mentioned in the Koran), it is waiting for those who advise them , take their hand to guide them on the right way and to rid themselves from dust , sins , injustice and corruption in order to live in the world with security and safety. This study came to show the civilizations breakdown factors through stories in the Koran mentioned storytelling at Surah Al- Hijr, and provided the results of those who listen to the evidence of guidance and to God satisfaction (Glory be upon Him).
Keywords: factors; the collapse of civilizations; Quranic stories; Surat Al-Hijr; negligence; the world